The safety data sheets of the paint and coatings sector: analysis of the items of most interest to health and safety in the workplace - Boniardi, Luca; Canti, Zulejka; Cantoni, Susanna; Fustinoni, Silvia (La Medicina del Lavoro, 2014)
Introduction: The interlinked REACH–CLP regulations promote the sharing of knowledge regarding the risks and hazards of chemicals throughout the supply chain. The safety data sheet (SDS) is the main instrument to achieve this goal. Objective: to study 100 SDS of paints and coatings sector in order to highlight major criticisms related to health and safety of workers. Materials and Methods: Using the criteria prescribed by Regulation 453/2010/EC and preparing a suitable check list, some items of the sections 1 “Identification of the substance/mixture and of the company“, 2 “Hazards identification”, 3 “Composition/information on ingredients”, the first part of section 7 “Precautions for safe handling”, sections 8 “Exposure controls/personal protection” and 16 “Other information”, were therefore evaluated for their appropriateness. Results: Seven SDS were written in a foreign language and were excluded from further analysis. Of the remaining 93 SDS, only 23% had a proportion of adequate items greater than 80%, 49 % had adequate items between 60 and 80%, and 28% had less than 60% adequate items. The most critical sections were those relating to workers’ safe handling and exposure controls and protection. Conclusion: In conclusion, from the analysis of SDS we found high percentages of inadequacy, especially in sections 7 and 8, the most relevant for the protection of the health and safety of workers.